Egy fictio és a merchandising szerződés - Strihó Krisztina (2009)
One aspect of the legal situation and chances of a fictitious sportsman are presented in this study. For this reason the merchandising contract and the sponsorship contract is compared in the part following the introduction. In the second part one special field of the merchandising contract is described from the two analised contracts: we take part in an imaginary commercial as a sportsman (because the commercial utilization appears tipically in the advertising legal relationship). We refer to the economic importance of the merchandising contract and necessity of the settlement of the applicable provision according to the social and economic claim (for the definition of the place in the legal system; the creation of the precise rules, just like in a form of an independent and consistent law).
Keywords: Társadalomtudományok; Jogtudomány